Gallic acid-based indanone derivative interacts synergistically with tetracycline by inhibiting efflux pump in multidrug resistant E. coli - Dwivedi, Gaurav Raj; Tiwari, Nimisha; Singh, Aastha; Kumar, Akhil; Roy, Sudeep; Negi, Arvind Singh; Pal, Anirban; Chanda, Debabrata; Sharma, Ashok; Darokar, Mahendra P (Applied microbiology and biotechnology, 2016)
The purpose of the present study was to study the synergy potential of gallic acid-based derivatives in combination with conventional antibiotics using multidrug resistant cultures of Escherichia coli. Gallic acid-based derivatives significantly reduced the MIC of tetracycline against multidrug resistant clinical isolate of E. coli. The best representative, 3-(3',4,'5'-trimethoxyphenyl)-4,5,6-trimethoxyindanone-1, an indanone derivative of gallic acid, was observed to inhibit ethidium bromide efflux and ATPase which was also supported by in silico docking. This derivative extended the post-antibiotic effect and decreased the mutation prevention concentration of tetracycline. This derivative in combination with TET was able to reduce the concentration of TNFα up to 18-fold in Swiss albino mice. This derivative was nontoxic and well tolerated up to 300 mg/kg dose in subacute oral toxicity study in mice. This is the first report of gallic acid-based indanone derivative as drug resistance reversal agent acting through ATP-dependent efflux pump inhibition.
Keywords: Gallic acid; Administration, Oral; Efflux pump inhibition; modely nemocí na zvířatech; Subacute oral toxicity; Indanone derivative; antibakteriální látky; aplikace orální; Microbial Sensitivity Tests; Indans; Escherichia coli; Enzyme Inhibitors; Molecular Docking Simulation; Drug Synergism; nežádoucí účinky léčiv; synergismus léků; simulace molekulového dockingu; Gallic Acid; kyselina gallová; Animals; Shock, Septic; Anti-Bacterial Agents; tetracyklin; septický šok; zvířata; mikrobiální testy citlivosti; makrofágy; Tetracycline; Disease Models, Animal; indany; Synergy; myši; Mice; Drug-Related Side Effects and Adverse Reactions; Macrophages; ATPase; inhibitory enzymů